Study on Thermophysical Properties of a Lead–Bismuth-Based Graphene Nanofluid - Yang, Tao; Zhao, Pengcheng; Li, Qiong; Zhao, Yanan; Yu, Tao (Frontiers in Energy Research, 2021)
Incorporating graphene nanoparticles with high thermal conductivity into a lead-based coolant can significantly increase its thermal conductivity and specific heat capacity, thereby increasing the core power density of lead–bismuth cooled reactors, reducing the amount of coolant required, and ultimately realizing a miniaturized and lightweight reactor design. The purpose of the design is of great significance to the engineering application of lead–bismuth stacks in remote areas and open seas. In this study, the thermophysical properties of metal-based graphene nanofluids are analyzed by comparing and analyzing prediction models established for the thermal conductivity, viscosity, and specific heat capacity. The strengthening mechanism of nanofluids is summarized, and a series of suitable calculation formulae for the thermophysical properties of lead–bismuth-based graphene nanofluids is proposed. The research results show that incorporating graphene nanoparticles into a lead–bismuth-based coolant can significantly improve its thermal conductivity and specific heat capacity. When the nanoparticle suspension is relatively stable, the thermal conductivity, specific heat capacity, and viscosity increase significantly with the concentration of graphene nanoparticles. When the concentration reaches 20%, the thermal conductivity and specific heat capacity of the nanofluid are enhanced by approximately 80 and 20%, respectively, whereas the viscosity is also increased by approximately 100%. Therefore, it is important to appropriately select the parameters for the addition of nanoparticles to maximize the effect of lead–bismuth-based graphene nanofluids on the heat transfer performance of the reactor core.